Results 1 to 6 of 6

Math Help - Composition/Image Proof

  1. #1
    Senior Member
    Joined
    Apr 2008
    From
    Vermont
    Posts
    318

    Composition/Image Proof

    If f:A→B is 1-1 and im f=B prove that (f^-1 ○f)(a)=a for all a element of A and (f^-1 ○f)(b)=b for each b an element of B.


    Here is what I've got out of this.
    f is 1-1, so for each b, there is one and only a. So f^-1(b)=a
    Im f=b. Thus, f is onto. Therefore, the range is equal to the set B. Would this imply f(a)=b and f(b)=b?

    I'm just not sure where to go with this problem.
    Follow Math Help Forum on Facebook and Google+

  2. #2
    MHF Contributor
    Joined
    Apr 2008
    Posts
    1,092
    Suppose f(x) = y.
    Then f^{-1}(y) = x.

    So f^{-1}(f(x)) = f^{-1}(y) = x.

    Similarly,
    f^{-1}(y) = x gives us
    f(x) = y.

    So f(f^{-1}(y)) = f(x) = y.
    Follow Math Help Forum on Facebook and Google+

  3. #3
    Senior Member
    Joined
    Apr 2008
    From
    Vermont
    Posts
    318
    Quote Originally Posted by icemanfan View Post
    Suppose f(x) = y.
    Then f^{-1}(y) = x.

    So f^{-1}(f(x)) = f^{-1}(y) = x.

    Similarly,
    f^{-1}(y) = x gives us
    f(x) = y.

    So f(f^{-1}(y)) = f(x) = y.
    How does the im F=B work into the proof? I don't get that part.
    Follow Math Help Forum on Facebook and Google+

  4. #4
    MHF Contributor

    Joined
    Aug 2006
    Posts
    18,922
    Thanks
    1762
    Awards
    1
    Quote Originally Posted by kathrynmath View Post
    How does the im F=B work into the proof? I don't get that part.
    One reason I did not respond before now is that I consider this question to have notational problems. Those problems are reflected in the icemanfanís answer, he assumed the ordinary meaning of the symbols.

    However is these set theory proofs, f^{ - 1} (b) = \left\{ {x \in A:f(x) = b} \right\}. That is the inverse image is a set.
    The fact that f is a bijection simply means that \left( {\forall b \in B} \right)\left[ {f^{ - 1} (b) \ne \emptyset } \right].
    By injectivity \left\{ {p,q} \right\} \subseteq f^{ - 1} (b) \Rightarrow \quad f(p) = f(q) = b \Rightarrow \quad p = q.
    Which means that each f^{-1}(b) is a singleton set.
    So \left( {\forall a \in A} \right)\left[ {f(a) \in B} \right] \Rightarrow \quad \left\{ a \right\} = f^{ - 1} \left( {f(a)} \right).

    Now I understand that this notation is not what the question implies.
    However, I hope it may give you some guidance.
    Follow Math Help Forum on Facebook and Google+

  5. #5
    MHF Contributor
    Joined
    Apr 2008
    Posts
    1,092
    Quote Originally Posted by kathrynmath View Post
    How does the im F=B work into the proof? I don't get that part.
    That just means that all of the elements of B are values that can be output by F. Hence, F is a bijection, and all elements of B have inverses of F in A.
    Follow Math Help Forum on Facebook and Google+

  6. #6
    Senior Member
    Joined
    Apr 2008
    From
    Vermont
    Posts
    318
    Thanks, I think I got the right idea to finish the problem now.
    Follow Math Help Forum on Facebook and Google+

Similar Math Help Forum Discussions

  1. Pre-Image / Image proof
    Posted in the Differential Geometry Forum
    Replies: 1
    Last Post: March 9th 2012, 03:30 AM
  2. Replies: 3
    Last Post: April 28th 2010, 09:40 PM
  3. Proof of being onto given a composition is onto?
    Posted in the Advanced Algebra Forum
    Replies: 1
    Last Post: February 19th 2010, 07:06 PM
  4. proof about composition
    Posted in the Discrete Math Forum
    Replies: 3
    Last Post: December 12th 2009, 05:54 PM
  5. Help with composition proof
    Posted in the Discrete Math Forum
    Replies: 1
    Last Post: September 20th 2009, 02:09 PM

Search Tags


/mathhelpforum @mathhelpforum